Language change and stance in a remote Mennonite community in Canada - Neuhausen, Miriam (Global and local perspectives on language contact, 2024)
This edited volume pays tribute to traditional and innovative language contact research, bringing together contributors with expertise on different languages examining general phenomena of language contact and specific linguistic features which arise in language contact scenarios. A particular focus lies on contact between languages of unbalanced political and symbolic power, language contact and group identity, and the linguistic and societal implications of language contact settings, especially considering contemporary global migration streams. Drawing on various methodological approaches, among others, corpus and contrastive linguistics, linguistic landscapes, sociolinguistic interviews, and ethnographic fieldwork, the contributions describe phenomena of language contact between and with Romance languages, Semitic languages, and English(es).